Electrosynthesis of Flavanones via oxa-Michael Addition Using Sacrificial Electrodes - Santos, William A. B.; de Castro, Pedro P.; Xavier, Fernando R.; Braga, Antonio L.; Martins, Guilherme M.; Mendes, Samuel R. (Synthesis, 2023)
An electrochemical synthesis of flavanones via oxa-Michael addition using silver electrode as a sacrifice is reported. This electrosynthetic system showed good yields, broad substrate scope, and good functional group tolerance. Additionally, the method proved to be applicable on a gram-scale. Several studies were carried out to elucidate the reaction mechanism, such as control reactions, cyclic voltammetry, and theoretical studies, allowing the proposal of a plausible pathway for this transformation.
Keywords: electrosynthesis; sacrificial electrodes; silver; flavonoids; cyclization